The Impact of the Use of Digital Games on the Development of Creative Thinking and Problem-solving Skills with Mathematics Disabilities in the State of Kuwait - Al-Huwailah أمثال هادي (Dirasat: Human and Social Sciences, 2023)
Objectives: The current study aimed to test the effectiveness of a digital games program as an input to improve some creative thinking and problem-solving skills for people with mathematical difficulties. Methods: A semi-experimental approach and a one-group experimental design were used. The main study sample included (30) people with math difficulties as an experimental group, and another (30) as a control sample; their ages ranged between (8-11) years. The Mathematics Learning Difficulties scale, the creative thinking test in mathematics, and the problem-solving ability scale were applied in addition to the program used. Results: The results revealed that there were statistically significant differences between the mean scores of the experimental and control groups on the two scales of creative thinking skills and problem-solving in the post-measurement, favoring the experimental group. It was also found that there were significant differences in the mean scores of creative thinking and problem-solving skills between the post and pre-applications of the experimental sample, where the mean scores of the experimental sample on the post-application were higher. It was also noted that there were no significant differences between the post and follow-up measurements (after four weeks of applying the program) for the experimental group in the mean scores of creative thinking and problem-solving skills. Conclusions: It was concluded that digital games improve creative thinking and problem-solving skills for those with mathematical difficulties, and thus reduce the levels of mathematics learning difficulties for these students.